Ancient Mesoamerican population history urbanism, social complexity, and change - Chase, Adrian S. Z. 1989-; Chase, Arlen Frank 1953-; Chase, Diane Elizabeth Zaino 1953- (University of Arizona Press, 2024)
"This book critically re-examines Mesoamerican archaeological approaches to estimating populations associated with ancient cities, settlement systems, and regions. Archaeological data and lidar are both employed to demonstrate how complex ancient Mesoamerican societies were and how they changed over time."
Keywords: Stadt; Bevölkerungsentwicklung; Siedlung; Mesoamerika; Demographic archaeology / Central America; Demographic archaeology / Mexico; Indians of Central America / Population; Indians of Mexico / Population; Demographic archaeology; Central America; Mexico; Aufsatzsammlung